Tandem Transesterification–Esterification Reactions Using a Hydrophilic Sulfonated Silica Catalyst for the Synthesis of Wintergreen Oil from Acetylsalicylic Acid Promoted by Microwave Irradiation - Barbosa, Sandro L.; Nelson, David Lee; Freitas, Milton de S.; dos Santos, Wallans Torres Pio; Klein, Stanlei I. [UNESP]; Clososki, Giuliano C.; Caires, Franco J.; Wentz, Alexandre P. (MDPI, 2022)
SiO2–SO3H, with a surface area of 115 m2/g and pore volume of 0.38 cm3g−1, and 1.32 mmol H+/g was used as a 20% w/w catalyst for the preparation of methyl salicylate (wintergreen oil or MS) from acetylsalicylic acid (ASA). A 94% conversion was achieved in a microwave reactor over 40 min at 120 °C in MeOH. The resulting crude product was purified by flash chromatography. The catalyst could be reused three times.
Keywords: deacetylation (acyl nucleophilic substitution); green chemistry; methyl salicylate; methylating agent; solid acid catalyst; sulfonated silica catalyst (SiO2–SO3H)